Posted by Kalleigh on Sunday, June 26, 2011 at 8:34pm.
The equations are the same (divide the second equation by 2). There is no solution.
to do substitution: you choose one equation, then represent one of the variables in terms in terms of the other. and finally substitute it the the other equation.
(1) x - 5y = 10
(2) 2x - 10y = 20
here, let's choose equation (1), and let's represent x in terms of variable y:
x - 5y = 10
x = 5y + 10
then we substitute this to equation (2):
2x - 10y = 20
2(5y + 10) - 10y = 20
10y + 20 - 10y = 20
20 = 20
note that when you come with this answer (constant = constant), this means that the lines are coinciding, meaning any point can be a solution, because the equations are "equal". if you observe equation (2), we can factor out 2:
2x - 10y = 20
2(x - 5y) = 2(10)
x - 5y = 10
it becomes equation (1).
hope this helps~ :)
X+4y=8
2x-5y=29